PENGEMBANGAN BAHAN AJAR KALKULUS PEUBAH BANYAK 1 (KPB 1) BERBASIS E-LEARNING - ISRA NURMAI YENTI (Ta'dib, 2010)
This study was aimed at producing valid e-learning based instructional materials. A Research and Development designed was used. There were two phase were employed; front-back analysis and prototype. The result of front-back analysis showed that the students needed instructional materials to help them imagine surface form. Consequently, instructional materials were designed on the basis of e-learning. Then, validation was conducted by consulting three validators. The result of validation by relevant experts showed that the e-learning based instructional materials were valid both in terms of construct and content.Kata kunci: pengembangan, bahan ajar, e-learning, KPB 1.